2022
DOI: 10.3390/ma16010123
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanical Properties of Cu–Al–Mn Alloys Fabricated by Electron Beam Additive Manufacturing

Abstract: In this work, the method of electron beam additive manufacturing (EBAM) was used to fabricate a Cu-based alloy possessing a shape memory effect. Electron beam additive technology is especially relevant for copper and its alloys since the process is carried out in a vacuum, which makes it possible to circumvent oxidation. The main purpose of the study was to establish the influence of the printing parameters on the structure of the obtained products, their phase composition, mechanical properties, dry friction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…C alloys had the least amount of the precipitate phases and relatively finer average grain structures and this may be responsible for their lower COF values. This result is by those reported by Haleem et al [17], Moskvichev et al [19], and Mohan et al [22] where it was established that wear properties of Cu-based SMAs are sensitive to the alloy composition and microstructures. The study thus concludes that the type of quenching treatment and alloy composition had an impact on wear performance since samples with a soft phase had a lower CoF.…”
Section: Wear Behavior Of Cu-zn-sn-based Smassupporting
confidence: 83%
See 1 more Smart Citation
“…C alloys had the least amount of the precipitate phases and relatively finer average grain structures and this may be responsible for their lower COF values. This result is by those reported by Haleem et al [17], Moskvichev et al [19], and Mohan et al [22] where it was established that wear properties of Cu-based SMAs are sensitive to the alloy composition and microstructures. The study thus concludes that the type of quenching treatment and alloy composition had an impact on wear performance since samples with a soft phase had a lower CoF.…”
Section: Wear Behavior Of Cu-zn-sn-based Smassupporting
confidence: 83%
“…Prashantha et al [18] showed that the wear behavior of Cu-Al-Be SMA is significantly influenced by their surface properties such as their abrasive, adhesive, and surface fatigue characteristics. Moskvichev et al [19] studied the wear behavior of Cu-Al-Mn SMA. The coefficient of friction is observed to be sensitive to the amount of soft a-phase which is dependent on the alloy composition, particularly on Mn concentration.…”
Section: Introductionmentioning
confidence: 99%